2006
DOI: 10.1007/s10340-006-0132-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent functional response of two aphid parasitoids, Aphidius colemani and Aphidius matricariae (Hymenoptera: Aphidiidae), on the cotton aphid

Abstract: The functional response of two aphid parasitoids, Aphidius colemani Viereck and Aphidius matricariae (Haliday) (Hymenoptera: Aphidiidae), on the cotton aphid, Aphis gossypii Glover (Homoptera: Aphididae), was examined. Five constant temperatures (10, 15, 20, 25, and 30°C) and six host densities (2, 4, 8, 16, 32, and 64) were used during a 24-h period. At each temperature, 2-64 third-instar nymphs of A. gossypii were exposed to individual wasp mating pairs. A type II functional response model for both paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 22 publications
9
55
3
3
Order By: Relevance
“…These results are consistent with the fi nding of a previous study by Feng et al (2014), which report a Holling's Type II response for A. bambawalei attacking third instar nymphs of P. solenopsis at 27 ± 1°C, relative humidity of 70 ± 5% and a photoperiod of 12L : 12D. Several researchers have also studied the effects of constant temperature on the functional response of parasitoids of different species of mealybugs (Flinn, 1991;Joens et al, 2003;Zamani et al, 2006 Functional responses are usually considered to be an important factor in the selection of the most suitable biocontrol agents. Type II functional response is theoretically less capable of suppressing host density compared to the type III functional response (Holling, 1965).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the fi nding of a previous study by Feng et al (2014), which report a Holling's Type II response for A. bambawalei attacking third instar nymphs of P. solenopsis at 27 ± 1°C, relative humidity of 70 ± 5% and a photoperiod of 12L : 12D. Several researchers have also studied the effects of constant temperature on the functional response of parasitoids of different species of mealybugs (Flinn, 1991;Joens et al, 2003;Zamani et al, 2006 Functional responses are usually considered to be an important factor in the selection of the most suitable biocontrol agents. Type II functional response is theoretically less capable of suppressing host density compared to the type III functional response (Holling, 1965).…”
Section: Discussionsupporting
confidence: 91%
“…However, there was a signifi cant decrease in handling time with increase in temperature, which means that at high temperatures there is more time available for searching and a greater probability of fi nding more hosts. Similar fi ndings are reported by Flinn (1991), Menon et al (2002), Jones et al (2003), Zamani et al (2006) and ZandiSohani et al (2008).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, our results indicate that searching behavior of A. certus is not random but systematic. Similarly, the type II functional response for Aphidius colemani and A. matricariae to the cotton aphid is best described using HollingÕs disc equation rather than the random predator equation (Zamani et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…) increases exponentially with warming, as predicted by MTE (Zamani et al 2006, Jalali et al 2010, Sentis et al 2012, while two recent meta-analyses reported that this relationship is hump shaped, with a thermal optimum (Englund et al 2011, Rall et al 2012). For both meta-analyses, the authors concluded that high temperatures reduce metabolic reaction rates, suggesting that the MTE equation is not appropriate to predict the effect of temperature on maximum intake rate over large temperature ranges.…”
mentioning
confidence: 99%